DIMENSI KENDARAAN RENCANA YANG OPERASIONAL - Erwin Kusnandar (Jurnal Jalan-Jembatan, 2007)
As a result of development and in line with the recent progress of technology, transportation sector is indicating the increase in number and changing in vehicle characteristic. The vehicle characteristic is changing vary from shape, dimension, and capacity. The change of those technical vehicle element, will influence geometric planning parameter of roadway which have been established in Bina Marga Guidance Of Road and Street Geometry Planning Procedures (1997). With those tendencies mentioned, technical design of yielded road and geometry cannot fulfill requirement of design vehicle traffic movements, resulting in traffic obstructions and accident possibilities. How far is the differencial gap between dimensional technical elements of designed vehicle, contained in the guidance and the actual operational vehicles. This study describes the research result, which indicates the existence of significant shifting in front and rear overhang length of truck and buses. Key Word : Design Vehicle,Element of Design Vehicle, and Operational Vehicle